PENYULUHAN DAN PELATIHAN POTENSI TANAMAN ZINGEBER OFFICINALE SEBAGAI PRODUK KESEHATAN INSTAN UNTUK MENGATASI ANTIFLAMASI - Sagita, Desi; Rudheka, Afrudi; Pratiwi, Anis; A, Eva; M, Putri; WH, Hani; RS, Miftah; G, Sri; A, Widya (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Traditionally people use ginger rhizome by boiling. To overcome these problems, and innovation made by making instant drinks with ginger rhizome raw materials. This community service is the application of the results of research conducted on ginger rhizomes in the form of powder, material from the plant's parts show activities that can relieve pain found in ginger rhizome extract. Community service carries out by utilizing the ginger rhizome to be used as a natural anti-inflammatory in the form of instant powder. The community service carries out by providing information and product-making demonstrations. Participants expected to increase knowledge about the benefits of the ginger rhizomes that are widely grown in the area, so that the community can utilize the ginger plant parts directly for use as an anti-inflammatory and can increase endurance in the form of instant powders. The results of the community service that carries out have enthusiastic people to take part in counseling and demonstrations on the production of instant ginger rhizome products.